Exploring sexual health information technology adoption intention: a systematic review through the lens of UTAUT - Zhang, Xin; Kamarudin, Syafila; Abdul Manaf, Rosliza; Tang, Qingqing (EAI, 2024)
Sexual health is a global concern, often exacerbated by inadequate information and services. Information technology (IT) has the potential to bridge this gap, but its adoption is influenced by various factors. Therefore, it is crucial to understand the impact of these factors on the adoption of sexual health IT. This investigation analyzed the factors that affect users' adoption intentions in sexual health IT using UAUT. Moreover, this study aimed to recognize the primary objectives in the research field and the study's constraints. By undertaking a systematic literature review following the PRISMA guidelines, we explored literature from January 2013 to November 2023. We extensively searched eight databases to identify UTAUT-relevant studies on sexual health IT adoption. Subsequently, we selected six high-quality articles for a detailed evaluation. The results indicate that the intention to adopt sexual health information technology is influenced by several factors, such as Effort Expectancy, Performance Expectancy, Social Influence, Facilitating Conditions, and Habits. Furthermore, Facilitating Conditions, behavioral intentions, and habits can directly influence adoption behaviors. Specifically, effort expectations and performance expectations are critical in influencing intentions. Future research should incorporate additional factors to explore the adoption of sexual health IT to improve our understanding of this area.